The Impact of Digital Literacy on 三级的生词 (Third-Level Vocabulary) in Mandarin Language Learners - Aiga Ventivani; Karina Fefi Laksana Sakti; Dhevy Olivia Firdaus; Galuh Bunga Usadani; Miftachul Amri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
In the context of language learning, including Mandarin education in Indonesia, digital literacy provides substantial benefits such as broader access to diverse learning resources, interactive learning opportunities, and more personalized learning experiences, while vocabulary mastery remains a fundamental component of language acquisition because it underpins learners’ ability to comprehend and use the target language effectively. However, although digital literacy has been widely examined in general educational settings, empirical evidence that specifically links digital literacy to HSK Level 3 (三级) vocabulary mastery (三级的生词) among first-year Mandarin students remains limited; therefore, this study addresses this gap by investigating (1) students’ digital literacy levels, (2) their mastery of HSK 3 vocabulary, and (3) the relationship between the two variables among Mandarin Language Study Program students. Using a quantitative survey design, primary numerical data were collected from 205 respondents and analyzed statistically. The results indicate that digital literacy significantly predicts HSK 3 vocabulary mastery (p < 0.05) and demonstrates substantial explanatory power: based on the proportion of regression sum of squares to total sum of squares (13,093.326 / 15,307.395), the model accounts for approximately 85.5% of the variance in vocabulary mastery, with strong overall model fit (F = 1200.480). These findings suggest that higher digital literacy is associated with better HSK 3 vocabulary mastery, highlighting digital literacy as a key factor in supporting successful Mandarin learning in digitally mediated environments and providing evidence to inform more targeted digital-literacy strengthening to optimize students’ use of learning applications, educational videos, and digital dictionaries.